Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0414
|View full text |Cite
|
Sign up to set email alerts
|

Animal Memory and Cognition

Abstract: Behaviorism, a dominant movement in animal learning until about 1970, emphasized that the subject matter of psychology is behavior. Originating about 1970 was a concern with animal cognition, a movement that emphasized to a considerable extent laboratory investigations in animals of processes commonly attributed to humans such as serial learning, numerical processes, categorization, inference formation, rule learning, and language learning. This approach, which is very much alive at present, assumes that anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…John's interest in animal cognition, and his constant pursuit of knowledge, led him to begin to explore the arguments coming from cognitive ethology and evolutionary psychology. John often cited specific species-typical behaviors as evidence in favor of evolutionary as well as associative approaches to understanding animal (including human) behavior (Capaldi, 2003;Capaldi & Martins, 2013). His final cohort of graduate students included three students interested in evolutionary approaches to human behavior.…”
Section: Interest In Evolutionary Theory and Scientific Methodologymentioning
confidence: 99%
“…John's interest in animal cognition, and his constant pursuit of knowledge, led him to begin to explore the arguments coming from cognitive ethology and evolutionary psychology. John often cited specific species-typical behaviors as evidence in favor of evolutionary as well as associative approaches to understanding animal (including human) behavior (Capaldi, 2003;Capaldi & Martins, 2013). His final cohort of graduate students included three students interested in evolutionary approaches to human behavior.…”
Section: Interest In Evolutionary Theory and Scientific Methodologymentioning
confidence: 99%
“…This means that fewer subgoals and, therefore, fewer steps are necessary to solve a problem ( Bayazitoglu et al., 1993 ). Chunking has also been proposed to be a form of the brain's categorization or organization ( Capaldi, 2003 ; Fonollosa et al., 2015 ).…”
Section: Memory Strategiesmentioning
confidence: 99%
“…For example, Macuda and Roberts (1995) indicated that rats use chunking in a spatial memory task (i.e., radial maze) when it is possible and this improves their performance. In a review of literature, Capaldi (2003) described three different sorts of chunks of varying degrees of complexity (i.e., trial , series , and list ) and maintained that rates are able to use all of them. The first and second types of chunking described by him (i.e., trial, series) are respectively what have been called simple and hierarchical chunking in the present review.…”
Section: Memory Strategiesmentioning
confidence: 99%